En Studie av inre splittring. Jaget i Erik Lindegrens diktsamling mannen utan väg - Rosińska, Paulina (Folia Scandinavica Posnaniensia, 2007)
Erik Lindegren’s volume 'mannen utan vag' ('the man without a way’, 1942/1945) is considered the most significant work of the Swedish 40s. The volume consists of forty sonnets. They are identical as regards their form, but the traditional structure of sonnet has been 'blown up' here. Such a new form, which combines pure harmony and disintegration, corresponds with the created reality: a world contaminated by evil. A metaphorical equivalent of this world is the ‘room of mirrors’, described in the first sonnet. All these circumstances influence the protagonist, not only the way in which he appears in the particular poems, but also his psyche. While living in the room of mirrors, he disintegrates into many different images. Each of them represents an attitude, which is often in sharp contrast to the other ones. As a modernist, Erik Lindegren believed that the truth is hidden in subjective visions. Therefore, the man without a way seems to symbolise a universal human nature consisting of many personalities